The patient encounter index: a novel method of measuring clinical workload in a paediatric cardiology service. (7th January 2020) - Harrison, Michael J.; Barry, Oliver M.; Hounsell, Rachel A.; De Decker, Rik
Abstract: Technological advances have led to better patient outcomes and the expansion of clinical services in paediatric cardiology. This expansion creates an ever-growing workload for clinicians, which has led to workflow and staffing issues that need to be addressed. The objective of this study was the development of a novel tool to measure the clinical workload of a paediatric cardiology service in Cape Town, South Africa: The patient encounter index is a tool designed to quantify clinical workload. It is defined as a ratio of the measured duration of clinical work to the total time available for such work. This index was implemented as part of a prospective cross-sectional study design. Clinical workload data were collected over a 10-day period using time-and-motion sampling. Clinicians were contractually expected to spend 50% of their daily workload on patient care. The median patient encounter index for the Western Cape Paediatric Cardiac Service was 0.81 (range 0.19–1.09), reflecting that 81% of total contractual working time was spent on clinical activities. This study describes the development and implementation of a novel tool for clinical workload quantification and describes its application to a busy paediatric cardiology service in Cape Town, South Africa. This tool prospectively quantifies clinical workload which may directly influence patient outcomes. Implementation of this novel tool in the described setting clearly demonstrated the excessive workload of the clinical service and facilitated effective motivation for improved allocation of resources.